Local connectivity and maps onto non-metrizable arcs - J. Nikiel; L. B. Treybig; H. M. Tuncali (International Journal of Mathematics and Mathematical Sciences)
Three classes of locally connected continua which admit sufficiently many maps onto non-metric arcs are investigated. It is proved that all continua in those classes are continuous images of arcs and, therefore, have other quite nice properties.